Synchronous diversification of Sulawesi's iconic artiodactyls driven by recent geological events. Issue 1876 (11th April 2018) - Frantz, Laurent A. F.; Rudzinski, Anna; Nugraha, Abang Mansyursyah Surya; Evin, Allowen; Burton, James; Hulme-Beaman, Ardern; Linderholm, Anna; Barnett, Ross; Vega, Rodrigo; Irving-Pease, Evan K.; Haile, James; Allen, Richard; et al.
Abstract : The high degree of endemism on Sulawesi has previously been suggested to have vicariant origins, dating back to 40 Ma. Recent studies, however, suggest that much of Sulawesi's fauna assembled over the last 15 Myr. Here, we test the hypothesis that more recent uplift of previously submerged portions of land on Sulawesi promoted diversification and that much of its faunal assemblage is much younger than the island itself. To do so, we combined palaeogeographical reconstructions with genetic and morphometric datasets derived from Sulawesi's three largest mammals: the babirusa, anoa and Sulawesi warty pig. Our results indicate that although these species most likely colonized the area that is now Sulawesi at different times (14 Ma to 2–3 Ma), they experienced an almost synchronous expansion from the central part of the island. Geological reconstructions indicate that this area was above sea level for most of the last 4 Myr, unlike most parts of the island. We conclude that emergence of land on Sulawesi (approx. 1–2 Myr) may have allowed species to expand synchronously. Altogether, our results indicate that the establishment of the highly endemic faunal assemblage on Sulawesi was driven by geological events over the last few million years.